Coupling Research on Lubrication and Gear Dynamics Under Different-carrier Ferrofluids - Ren Fenglan; Wei Kun; Jian Guangxiao; Wang Youqiang (Jixie chuandong)
In order to explore the coupling effect of ferrofluids with different carriers on lubrication and gear dynamics, the dynamic model and the ferrofluid lubrication model of the gear system are established. Based on the fourth order Runge-Kutta method, the multi-grid method and multi-grid integration method, the influence of different-carrier ferrofluids on oil film and the distribution of dynamic loads are analyzed. The results show that the film forming characteristics of tooth surfaces can be improved by changing the magnetic fluid base carrier and increasing the magnetic fluid viscosity appropriately. It is mainly reflected in the increase of oil film thickness and stiffness between gear teeth and the decrease of oil film pressure and amplitude of oil film thickness under dynamic loads. When the viscosity of the magnetic fluid increases, the comprehensive stiffness of the gear system also increases. On the contrary, when the vibration speed of the gear pair and the amplitude of the dynamic loads decreased, the impact loads are eventually suppressed, and the dynamic characteristics and NVH（Noise Vibration Harshness） performance of the gear system are improved consequently.